2007
DOI: 10.1093/heapro/dam011
|View full text |Cite
|
Sign up to set email alerts
|

Organizational change--key to capacity building and effective health promotion

Abstract: Contemporary health promotion is now a well-defined discipline with a strong (albeit diverse) theoretical base, proven technologies (based on program planning) for addressing complex social problems, processes to guide practice and a body of evidence of efficacy and increasingly, effectiveness. Health promotion has evolved principally within the health sector where it is frequently considered optional rather than core business. To maximize effectiveness, quality health promotion technologies and practices need… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
76
0
5

Year Published

2012
2012
2019
2019

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(84 citation statements)
references
References 11 publications
2
76
0
5
Order By: Relevance
“…However, the enablers and barriers identified were common across the studies and despite these limitations there are several key findings that 21,22,25 -access to expertise, workforce development and training 21,22,25 -recruitment of skilled staff 21,22,25 -priority given to health promotion approaches. 25,26 Influence on the organisation's ethos and practice: -aligning health promotion with the organisation's vision, values and priorities 20,27,28 -long term commitment to health promotion 26,29 -culture of collaboration 27,31 -sound knowledge of health promotion 30 -build on previous initiatives 25 -identify further funding 30 -embedding health promotion activities into planning and reporting, including quality improvement processes. 22 -proactive approach to staff development and succession planning 33 -support joint work with key stakeholders 33 External partnerships -access to external partners (key stakeholders including community members) to work on health promotion approaches 18,[25][26][27] can be explored further: management support, leadership, external specialist assistance, skilled staff, partnership work, resource allocation, and the challenge of competing work priorities in health organisations.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, the enablers and barriers identified were common across the studies and despite these limitations there are several key findings that 21,22,25 -access to expertise, workforce development and training 21,22,25 -recruitment of skilled staff 21,22,25 -priority given to health promotion approaches. 25,26 Influence on the organisation's ethos and practice: -aligning health promotion with the organisation's vision, values and priorities 20,27,28 -long term commitment to health promotion 26,29 -culture of collaboration 27,31 -sound knowledge of health promotion 30 -build on previous initiatives 25 -identify further funding 30 -embedding health promotion activities into planning and reporting, including quality improvement processes. 22 -proactive approach to staff development and succession planning 33 -support joint work with key stakeholders 33 External partnerships -access to external partners (key stakeholders including community members) to work on health promotion approaches 18,[25][26][27] can be explored further: management support, leadership, external specialist assistance, skilled staff, partnership work, resource allocation, and the challenge of competing work priorities in health organisations.…”
Section: Discussionmentioning
confidence: 99%
“…To increase organisational health promotion capacity, management support, 18,20-33 a skilled and knowledgeable workforce, [34][35][36][37][38] external specialist assistance, 18,24,32,34,35 resource allocation, 20,22,27,31 leadership 26,27,29,31,33,39,40 and access to external partners to work on health promotion approaches 21,[25][26][27] were the most commonly reported enablers. Management support was reported in two ways: first, the line manager's influence on work practice; and second, the influence of the organisation's ethos and practice.…”
Section: Enablers For Increasing Health Promotion Capacity Within Heamentioning
confidence: 99%
See 2 more Smart Citations
“…Augustine (2013) posited that for Firm Growth to be actualised, failing organisations should reconsider the capabilities of managers and insist on change where there are deficiencies irrespective of the complexities involved in change process. Confirming the complexities in change process, Heward et al (2007) observed that the planning of change becomes complex with many contingencies, steps and sub steps. In some cases, organisations may go through cycles of change without proper planning and implementation or worst still skip one or more steps of the action plan that may have been erroneously perceived as trivial.…”
Section: Literature Reviewmentioning
confidence: 90%